Synthesis, in vitro biological assessment, and molecular docking study of benzimidazole-based thiadiazole derivatives as dual inhibitors of α-amylase and α-glucosidase - Khan, Shoaib; Iqbal, Shahid; Taha, Muhammad; Hussain, Rafaqat; Rahim, Fazal; Shah, Mazloom; Awwad, Nasser S.; Ibrahium, Hala A.; Alahmdi, Mohammed Issa; Dera, Ayed A.; Ullah, Hayat; Bahadur, Ali; et al. (Frontiers in Chemistry, 2023)
The clinical significance of benzimidazole-containing drugs has increased in the current study, making them more effective scaffolds. These moieties have attracted strong research interest due to their diverse biological features. To examine their various biological significances, several research synthetic methodologies have recently been established for the synthesis of benzimidazole analogs. The present study aimed to efficiently and quickly synthesize a new series of benzimidazole analogs. Numerous spectroscopic techniques, including 1H-NMR, 13C-NMR, and HREI-MS, were used to confirm the synthesized compounds. To explore the inhibitory activity of the analogs against α-amylase and α-glucosidase, all derivatives (1–17) were assessed for their biological potential. Compared to the reference drug acarbose (IC50 = 8.24 ± 0.08 µM), almost all the derivatives showed promising activity. Among the tested series, analog 2 (IC50 = 1.10 ± 0.10 & 2.10 ± 0.10 µM, respectively) displayed better inhibitory activity. Following a thorough examination of the various substitution effects on the inhibitory capacity of α-amylase and α-glucosidase, the structure-activity relationship (SAR) was determined. We looked at the potential mechanism of how active substances interact with the catalytic cavity of the targeted enzymes in response to the experimental results of the anti-glucosidase and anti-amylase. Molecular docking provided us with information on the interactions that the active substances had with the various amino acid residues of the targeted enzymes for this purpose.